Carbene-Catalyzed Regioselective Addition of Oxindoles to Ynals for Quick Access to Allenes - Sun, Cuiyun; Nong, Yingling; Pang, Chen; Zhang, Sheng; Li, Tingting (Synlett, 2023)
A catalytic regioselective addition reaction of oxindoles with ynals is developed. Allene-containing derivatives bearing various substituents and substitution patterns are afforded as the products in generally moderate to good yields with moderate diastereoselectivities. Several of allenes obtained from this protocol are valuable in the development of novel bactericides for plant protection.
Keywords: N-heterocyclic carbene; regioselective addition; allene; organocatalysis; plant protection